2012
DOI: 10.1021/cb300541g
|View full text |Cite
|
Sign up to set email alerts
|

A Liver-Selective LXR Inverse Agonist That Suppresses Hepatic Steatosis

Abstract: Fatty liver, which often accompanies obesity and type 2 diabetes, frequently leads to a much more debilitating hepatic disease including non-alcoholic steatohepatitis, cirrhosis, and hepatocellular carcinoma. Current pharmacological therapies lack conclusive efficacy and thus treatment options are limited. Novel therapeutics that suppress either hepatic lipogenesis and/or hepatic inflammation may be useful. Here, we describe the development of the first selective synthetic LXR inverse agonist (SR9238) and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
128
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(139 citation statements)
references
References 30 publications
10
128
1
Order By: Relevance
“…A recent study found that the LXRa antagonist 22-S-hydroxycholesterol counteracted T090-induced lipogenesis and lipid formation in myotubes from type 2 diabetic patients (Kase et al, 2007). Hepatospecific inhibition of LXR using an inverse agonist also inhibited NAFLD development induced by a high-fat diet (Griffett et al, 2013). Published studies indicate that there is good correlation between the level of LXRa expression and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that the LXRa antagonist 22-S-hydroxycholesterol counteracted T090-induced lipogenesis and lipid formation in myotubes from type 2 diabetic patients (Kase et al, 2007). Hepatospecific inhibition of LXR using an inverse agonist also inhibited NAFLD development induced by a high-fat diet (Griffett et al, 2013). Published studies indicate that there is good correlation between the level of LXRa expression and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the grapefruit flavonoid naringenin inhibits ligand-induced LXRa activation by suppressing the action of Trap220 coactivator (Goldwasser et al, 2010). The synthetic LXR inverse agonist SR9238 increases the interaction between NCoR and LXR and decreases the Trap220 interaction (Griffett et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One of these candidates, SR9328, has been shown to suppress fat production, eliminate inflammation and reverse fat accumulation in mouse livers 3 . But researchers do not yet know how effective this drug will be in the presence of fibrosis and cirrhosis, which do not develop in these mice.…”
Section: Damage Controlmentioning
confidence: 99%
“…Unfortunately, the trial was terminated due to adverse central nervous system effects. [19][20][21] LXR antagonists reported so far include riccardin C (4, antagonist of LXRβ), naringenin (5, antagonist of LXRα), genistein (6, inhibition of LXRα or activation of LXRβ), taurine (7, antagonist of LXRα), rhein (8, antagonist of LXRα/β), SR-9238 (9, antagonist of LXRα/β), and 10 (antagonist of LXRα), among others [22][23][24][25][26][27][28] (Fig. 1).…”
mentioning
confidence: 99%
“…27) In this paper, we describe the discovery and further structural development of LXR antagonists based on the fibrate skeleton. Both molecules activated LXRs in a luciferase reporter gene assay (GAL4) tested in HEK-293 cells.…”
mentioning
confidence: 99%